Serum 25-Hydroxyvitamin D3 and BAFF Levels Are Associated with Disease Activity in Primary Sjogren’s Syndrome - Sang Jin Lee; Hye Jin Oh; Byoong Yong Choi; Yu Jin Jang; Joo Youn Lee; Jin Kyun Park; Yeong Wook Song (Journal of Immunology Research)
The study investigated the association between disease activity and serum 25-hydroxyvitamin D3 (25(OH)-D3), B cell activation of the tumor necrosis factor family (BAFF), or β2 microglobulin in patients with primary Sjogren’s syndrome (SS). Sixty-nine primary SS patients and 22 sicca control patients were included in the study. Disease activity was measured with EULAR Sjogren’s syndrome disease activity index (ESSDAI). Serum levels of 25(OH)-D3 and β2 microglobulin were measured by radioimmunoassay and BAFF was measured by an enzyme-linked immunosorbent assay. Serum levels of 25(OH)-D3 were significantly lower in SS patients compared to the sicca controls (p=0.036). Serum levels of BAFF tended to be higher (p=0.225) and those of β2 microglobulin were significantly higher in patients with SS than in sicca controls (p=0.023). In univariate regression analyses, ESSDAI was significantly associated with serum levels of 25(OH)-D3, BAFF, and β2 microglobulin. After stepwise backward multivariate linear regression analyses including age and acute phase reactants, ESSDAI was associated with 25(OH)-D3 (β = −0.042, p=0.015) and BAFF (β = 0.001, p=0.015) in SS patients. In SS patients, ESSDAI is negatively associated with serum levels of 25(OH)-D3 and positively associated with BAFF.